2017
DOI: 10.1167/iovs.16-20001
|View full text |Cite
|
Sign up to set email alerts
|

Functional Outcomes of the Low Vision Depression Prevention Trial in Age-Related Macular Degeneration

Abstract: PurposeTo compare the efficacy of behavioral activation (BA) plus low vision rehabilitation with an occupational therapist (OT-LVR) with supportive therapy (ST) on visual function in patients with age-related macular degeneration (AMD).MethodsSingle-masked, attention-controlled, randomized clinical trial with AMD patients with subsyndromal depressive symptoms (n = 188). All subjects had two outpatient low vision rehabilitation optometry visits, then were randomized to in-home BA + OT-LVR or ST. Behavioral acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…These findings are, overall, similar to what has previously been reported in other delivery models ( Figure ). The mobile clinic outcomes are most similar to those seen in LVROS and the Low Vision Depression Prevention Trial (VITAL), and are larger than some other outpatient LVR delivery models …”
Section: Discussionmentioning
confidence: 65%
“…These findings are, overall, similar to what has previously been reported in other delivery models ( Figure ). The mobile clinic outcomes are most similar to those seen in LVROS and the Low Vision Depression Prevention Trial (VITAL), and are larger than some other outpatient LVR delivery models …”
Section: Discussionmentioning
confidence: 65%
“…Their enhanced program involved a home visit from a rehabilitation officer, focused on ensuring accurate use of low vision aids by utilising additional in-home training and vision enhancing strategies such as with contrast and lighting and was found to confer no additional benefit. In contrast, Deemer et al 84 found that in-home occupational therapy low vision rehabilitation combined with behavioural activation therapy following conventional optometric low vision services demonstrated better functional outcomes than conventional rehabilitation alone. This randomised controlled trial encompassed goal-oriented rehabilitation that addressed both functional vision and psychosocial needs of the patient.…”
Section: Lvqolmentioning
confidence: 92%
“…1 It is the primary cause of loss of central vision and significantly decreases the individual's quality of life. In general, AMD is divided into early and late stages.…”
Section: Introductionmentioning
confidence: 99%